1999
DOI: 10.3354/meps182109
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages of sessile marine invertebrates:still changing after all these years?

Abstract: The fouling organisms on Port Bonython pier, South Australia, had previously been monitored for 6.5 yr after initial immersion of piles using photographs of fixed positions and direct observation by divers. Up to that date it appeared that predictions based on experiments at more sheltered sites had not been fulfilled. In particular, the assemblage had not become dominated by modular organisms The rate of change seemed to be slowing after 6.5 yr but this could not be tested. The assemblage on the piles was re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Predation (e.g., Connell & Anderson, 1999;Fairweather, 1988;Keough & Butler, 1979;Menge & Sutherland, 1976;Paine, 1966), competition and overgrowth among sessile organisms (e.g., Butler & Connolly, 1999;Connell, 1961;Jernakoff, 1985;Kay & Keough, 1981;Keough, 1984;Miles & Meslow, 1990) may be important factors in determining the distribution of Hydroides spp. on the sides of pontoons.…”
Section: Discussionmentioning
confidence: 99%
“…Predation (e.g., Connell & Anderson, 1999;Fairweather, 1988;Keough & Butler, 1979;Menge & Sutherland, 1976;Paine, 1966), competition and overgrowth among sessile organisms (e.g., Butler & Connolly, 1999;Connell, 1961;Jernakoff, 1985;Kay & Keough, 1981;Keough, 1984;Miles & Meslow, 1990) may be important factors in determining the distribution of Hydroides spp. on the sides of pontoons.…”
Section: Discussionmentioning
confidence: 99%
“…Sessile species, on the other hand, disperse mainly at larval or propagule stages and their distribution is more subject to the so-called "priority" effect. Several studies have demonstrated the highly variable distribution of sessile species on hard substrata, last but not least affected by stochastic events (Butler and connolly, 1999). the spatial turnover of such species is therefore more insensitive to patch size, whereas it decreases at larger scale as a possible consequence of the unsaturated "local" vs. "regional" space.…”
Section: Spatial and Taxonomic Species Turnover The Contribution Of mentioning
confidence: 99%
“…McDougal 1943, Osman 1977, Sutherland & Karlson 1977, Keough & Butler 1979, Kay & Keough 1981, Keough 1984a,b, Anderson & Underwood 1994, Osman & Whitlatch 1995a,b, Brown & Swearingen 1998, Butler & Connolly 1999, Glasby 2000. Therefore the processes structuring these assemblages are probably as well understood as those of any ecological assemblage.…”
Section: Introductionmentioning
confidence: 99%